The subject-subject education paradigm in the conditions of provincial higher school - V. V. Bulkin (Высшее образование в России)
Problems of transition of domestic higher education institutions to the subject-subject education paradigm are considered. Principles of the subject-subject education paradigm from the point of view of historically developed socio-cultural base of functioning of theRussian society are analyzed. The author proposes measures for upgrading the educationalprocess taking into account national socio-cultural environment.